Effects of EFL Teachers’ Scaffolding Strategies on Motivation and Grammatical Achievement: Pawi Secondary and Preparatory School, Grade 11 in focus - Gebeyehu, Amrach Melaku; Shifere, Kassie; Maru, Nururazik (ETHIOINQUIRY Journal of Humanities and Social Sciences, 2025)
The main objective of this study was to examine the effects of EFL teachers’ Scaffolding strategies on students’ motivation towards grammar learning and grammar achievement: Pawi Secondary and Preparatory School, Grade 11 in focus. To this end, the study employed a quasi-experimental research design with a quantitative approach. The school was selected using convenient sampling technique among six Secondary and Preparatory Schools in Pawi woreda. Two data collection instruments were used and piloted in the study. Participant students were selected using purposive sampling technique. In this study pre-test were given(for baseline) for all six sections and purposely selected two intact groups out of six which have homogenous pre-test results from grade 11 students, creating comparison and experimental groups. Each group consisted of 51 students, resulting in a total of 102 participants. Data were collected through pre- and post-tests for grammar achievement and motivation towards learning grammar questionnaire test for students. The findings analyzed using independent sample t-tests, and the results indicated that the treatment had a significant and noteworthy influence on both students’ motivation towards learning grammar and grammatical achievement. This shows that the implementation of scaffolding strategies by EFL teachers positively affected students’ motivation towards learning grammar and their ability to improve their grammatical achievement. Based on the results, the study provides valuable evidence supporting the effectiveness of EFL teachers’ scaffolding strategies in enhancing students’ motivation towards learning grammar and grammar achievement in the Ethiopian educational setting.